New globular cluster candidates in the M81 group. Issue 1 (16th June 2022) - Pan, Jiaming; Bell, Eric F; Smercina, Adam; Price, Paul; Slater, Colin T; Bailin, Jeremy; de Jong, Roelof S; D'Souza, Richard; Jang, In Sung; Monachesi, Antonela
ABSTRACT: The study of outer halo globular cluster (GC) populations can give insight into galaxy merging, GC accretion, and the origin of GCs. We use archival Subaru Hyper Suprime-Cam (HSC) data in concert with space-based GALEX, IRAC, and Gaia EDR3 data to select candidate GCs in the outer halo of the M81 group for confirmation and future study. We use a small sample of previously discovered GCs to tune our selection criteria, finding that bright already-known GCs in the M81 group have sizes that are typically slightly larger than the Subaru PSF in our fields. In the optical bands, GCs appear to have colours that are only slightly different from stars. The inclusion of archival IRAC data yields dramatic improvements in colour separation, as the long wavelength baseline aids somewhat in the separation from stars and clearly separates GCs from many compact background galaxies. We show that some previously spectroscopically identified GCs in the M81 group are instead foreground stars or background galaxies. GCs close to M82 have radial velocities, suggesting that they fell into the M81 group along with M82. The overall M81 GC luminosity function is similar to the Milky Way and M31. M81's outer halo GCs are similar to the Milky Way in their metallicities and numbers, and much less numerous than M31's more metal-rich outer halo GC population. These properties reflect differences in the three galaxies' merger histories, highlighting the possibility of using outer halo GCs to trace merger history in larger samples of galaxies.